2013
DOI: 10.1038/ismej.2013.119
|View full text |Cite
|
Sign up to set email alerts
|

Comparative metatranscriptomics reveals kingdom level changes in the rhizosphere microbiome of plants

Abstract: Plant-microbe interactions in the rhizosphere have important roles in biogeochemical cycling, and maintenance of plant health and productivity, yet remain poorly understood. Using RNA-based metatranscriptomics, the global active microbiomes were analysed in soil and rhizospheres of wheat, oat, pea and an oat mutant (sad1) deficient in production of anti-fungal avenacins. Rhizosphere microbiomes differed from bulk soil and between plant species. Pea (a legume) had a much stronger effect on the rhizosphere than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

27
321
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 475 publications
(350 citation statements)
references
References 63 publications
(69 reference statements)
27
321
0
2
Order By: Relevance
“…A drawback of the GeoChip is the fact that novel functions and transcripts cannot be identified, and one is biased to the probes present in the chip (Dugat-Bony et al, 2012). Recently, metatranscriptomics in soil has been attempted on the rRNA to identify the active members of the microbial community in the rhizosphere of various crop species (Turner et al, 2013); Urich et al (2008) described the isolation and sequencing of mRNA from a sandy lawn as a means of describing the microbial transcriptome in the soil. The rhizosphere microbiome plays an essential role in plant health and productivity and it is often referred as the plant's second genome (Berendsen et al, 2012;Chaparro et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…A drawback of the GeoChip is the fact that novel functions and transcripts cannot be identified, and one is biased to the probes present in the chip (Dugat-Bony et al, 2012). Recently, metatranscriptomics in soil has been attempted on the rRNA to identify the active members of the microbial community in the rhizosphere of various crop species (Turner et al, 2013); Urich et al (2008) described the isolation and sequencing of mRNA from a sandy lawn as a means of describing the microbial transcriptome in the soil. The rhizosphere microbiome plays an essential role in plant health and productivity and it is often referred as the plant's second genome (Berendsen et al, 2012;Chaparro et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…According to the UK Soil Observatory, the soil can be classified as Luvisol (WRB classification) and the soil texture was loamy with bits of chalk in the layer below the top layer. This soil was chosen as the history of its plant coverage is well documented and the microbial communities have been characterised in a previous study (Turner et al, 2013b).…”
Section: Methodsmentioning
confidence: 99%
“…However, interaction between plants and microbes is more general with plants shown to shape the rhizosphere microbiota in legumes, potatoes and suppressive soils (Sharma et al, 2005;Lebreton et al, 2007;Manter et al, 2010;Kinkel et al, 2011;Mendes et al, 2011;Turner et al, 2013b). Some microbial root colonists are saprophytes, which also colonise splinters of wood inserted into soil (Bulgarelli et al, 2012), but others are selected by exudation of nutrient sources and phytoalexins, such as glucosinolates and avenacins (Sonderby et al, 2007;Bressan et al, 2009;Turner et al, 2013b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies showed that aerated forest, rice field, grassland soil and rhizosphere soil can harbor diverse methylotrophic communities (Lueders et al 2004;Radajewski et al 2002;Turner et al 2013;Stacheter et al 2013;Eyice et al 2015).…”
Section: Introductionmentioning
confidence: 99%